2015
DOI: 10.1021/acs.est.5b00170
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Microcystis aeruginosa to Hydrogen Peroxide under Light: Kinetic Modeling of Cell Rupture and Simultaneous Microcystin Degradation

Abstract: The effect of hydrogen peroxide on the cell integrity of a cyanobacterium, Microcystis aeruginosa, and on the release and degradation of microcystins (MCs) under simulated sunlight was investigated. The cyanobacterium was exposed to H2O2 in the range of 0-60 mg·L(-1) for 3.5 h. Production of OH radical in the solution was estimated by a chemical probe method. More than 99% (2 log) of the M. aeruginosa cells were ruptured or damaged by 3 h for all the treatments. Loss of cell integrity over time revealed two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 63 publications
9
42
0
Order By: Relevance
“…the sum of particulate and water soluble fractions, rapidly decreased by more than 90 % in \3 days (Matthijs et al 2012). The latter observations on rapid MC degradation are supported by reports on microbial degradation of MC (Lawton et al 2011;Dziga et al 2013) and hydroxyl radical catalysed processing of microcystin (Huo et al 2015).…”
Section: Considerations About Hp Applicationsupporting
confidence: 69%
See 1 more Smart Citation
“…the sum of particulate and water soluble fractions, rapidly decreased by more than 90 % in \3 days (Matthijs et al 2012). The latter observations on rapid MC degradation are supported by reports on microbial degradation of MC (Lawton et al 2011;Dziga et al 2013) and hydroxyl radical catalysed processing of microcystin (Huo et al 2015).…”
Section: Considerations About Hp Applicationsupporting
confidence: 69%
“…This hypothesis was thereafter successfully tested in the laboratory (Dráb-ková et al 2007a, b;Weenink et al 2015) and in the field (Matthijs et al 2012). The actual cyanobacteria killing compound may very well be not HP itself but a compound derived from HP, for which hydroxyl radical formation by UV light and catalysed by Fenton reaction active ions has been presented as a candidate by Huo et al (2015).…”
Section: Mode Of Action Of Hydrogen Peroxidementioning
confidence: 99%
“…This kind of inhibition followed by regrowth of cyanobacteria during the application of H 2 O 2 has been reported by Qian et al (2010) [62], where M. aeruginosa grew after 96 h of exposure to a dose of 100 µM (3.4 mg·L −1 ) H 2 O 2 . In addition, Huo et al, (2015) [54] reported a two-stage in M. aeruginosa cell integrity change when exposed to H 2 O 2 under light illumination, with cell rupturing following the Delayed Chick−Watson Model, where before the lag time all cells remained integrated and after the lag time the cells started to be ruptured. Although the experiments in that study were only conducted for 6 h, much less than in the current work, their results demonstrated that Microcystis cells are not resistant to H 2 O 2 exposure with 99% of the Microcystis cells damaged within 3 h when exposed to 22.34 W·m −2 (solar irradiance at the surface of the water).…”
Section: Resultsmentioning
confidence: 99%
“…The present study shows that under the condition of light intensity = 2.3 W·m −2 and H 2 O 2 dose = 20 mg·L −1 , degradation of H 2 O 2 was three times faster in the sample with M. aeruginosa (2.3 × 10 6 cells/mL) than that in deionized water (Figure 1). Huo et al (2015) [54] [57] reported a general copper dose ranging from 0.025 to 1 mg·L −1 that can be used to achieve control of algae blooms. With lower copper sulfate doses, although slight inhibition was observed if compared with controlled samples, cells still grew within 14 days of the experiments (Figure 2a).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Understanding the quality of these waters is therefore an important issue to safeguard public health. Cyanobacteria are an important group of microorganisms present in lakes and reservoirs, and some produce toxins [1,2] and taste and odor compounds [3,4]. Microcystins (MCs) [cyclo-(D-Ala1-X2-D-MeAsp3-Z4-Adda5-D-Glu6-Mdha7)], a group of heptapeptide hepatotoxins, are produced by several cyanobacteria genus, such as Microcystis, Anabaena, Nostoc, and Planktothrix [5], and they are toxic to animals and humans [6,7].…”
Section: Introductionmentioning
confidence: 99%